Board games and Pancasila education: Teachers' perspectives in supporting global diversity - Merkuri, Yulia Gesti; Aulia, Syifa Siti; Talha Bin Nasim, Muhammad (Universitas Negeri Yogyakarta, 2025)
Global diversity is an important element in the era of globalisation to form students able to adapt to intercultural situations. Teachers as facilitators help students achieve this by paying attention to learning components such as the media used. Teachers must have the instinct that the media used must have an impact on knowledge and attitudes. So, it is necessary for teachers' perceptions regarding board game learning media to help develop media. This study aims to determine Pancasila Education teachers' perceptions of board game media in interactive learning based on global diversity. The study used a mixed method with a concurrent equal status model. Quantitative and qualitative instruments refer to three aspects of interactive learning (student engagement, independent learning and cognitive load). Quantitative data were obtained through surveys, while qualitative data were collected through semi-structured interviews to support quantitative findings. The subjects of the study were Pancasila Education teachers in 12 Muhammadiyah Junior High Schools/MTSs throughout the city of Yogyakarta. The results of the study showed that interactive board game media based on global diversity supports Pancasila education learning. Teachers provide the perception that board games need to be adjusted to the values of diversity and inclusion and based on high-order thinking skills, also need to provide collaborative challenges, positive reward and punishment systems, and independent tasks such as art projects or essays. The material must be relevant to students, have simple rules and be age-appropriate. Interactive learning can strengthen the appreciation of differences in views and cultures, preserve noble values and improve intercultural adaptation.